The social construction of state power : applying realist constructivism - Barkin, J. Samuel, 1965- (Bristol University Press, 2020)
Realism and constructivism are often viewed as competing paradigms for understanding international relations, though scholars are increasingly arguing that the two are compatible. Edited by one of the leading proponents of realist constructivism, this volume shows what realist constructivism looks like in practice by innovatively combining exposition and critiques of the realist constructivist approach with a series of international case studies. Each chapter addresses a key empirical question in international relations and provides important guidance for how to combine both approaches effectively in research. Addressing future directions and possibilities for realist constructivism in international relations, this book makes a significant contribution to the theorizing of global politics.